The impact of financial policy on economic growth in Jordan (2000-2017) : an ARDL approach - Alghusin, Nawaf Ahmad (Array, 2020)
The aim of this paper is to examine the impact of financial policy on rate of economic growth in Jordan for the period of (2000-2017) taking into the considerations the fluctuations of taxation system. Autoregressive Distributed Lag (ARDL) approach has been utilized in order to analyze the long term relationship between study variable which are; money supply (M2), domestic credit provided by banks (DCBS) and real Gross Domestic Product GDP. The results shows that, money (M2) and domestic credit provided by banks (DCBS) can effects on GDP in Jordan for the study period. The taxation system in Jordan has been fluctuated many times during 2017 and 2018, which made the data partly not available. This led the researchers to spend long time to find an accurate data in order to finalize this study. This study will add good practical evidence on the impact of changing the taxation system positively or negatively on the economic growth.